The federation of islamic medical associations (FIMA) 20th international camp for medical students 2022, Indonesia - Kamarudin, Intan Kartika (Faculty of Medicine, 2023)
Ten years 3 and 2 students from the Faculty of Medicine (FOM), Universiti Teknologi MARA (UiTM), were selected to be the delegates for the Islamic Medical Association Malaysia (IMAM) contingent of 12 to the 20th International Student Camp. The camp was held from the 29th of November until the 5th of December 2022 at Karang Anyar Regency, Indonesia. This camp was organized by the Islamic Medical Association in the Kingdom of Saudi Arabia (IMAKSA) and the World Assembly of Muslim Youth (WAMY) in collaboration with the Federation of Islamic Medical Associations, Students Affairs Council (FIMASAC), Indonesia Islamic Medical Association (IIMA) and University of Muhammadiyah in Yogyakarta (UMY). Following the theme, "Effective Habits of Successful and Influential Medical Professionals," this camp aimed to improve the heme, "Effective Habits of Successful and Influential Medical Professionals," this camp aimed to improve the abilities and skills of the participants in building networking, teamwork, and leadership.